PERBANDINGAN VCO, MINYAK ZAITUN DAN MINYAK JAGUNG TERHADAP SIFAT FISIK BALSEM STIK DENGAN PENGIKAT VASELIN ALBA ATAU ADEPS LANAE - Lestari, Pramulani Mulya; Yati, Kori; Rosanti, Mimil (Jurnal Farmasi Indonesia, 2019)
The use of balm by applying it to the affected part of the body can cause heat and stickiness in the fingers. Making balm sticks is one solution to overcome this problem. Balm sticks are influenced by the components used are oils, waxs and fats. Oils and fats have different fat acid and molecul weight will affect the physical properties of balm stick. Selection of the proper components are excepted to good melting point and hardness and in accordance with requirments. This study aimed at compare of VCO, olive oil and corn oil with variation between Adeps lanae and Vaselin albaon the physical properties of stick balm. All balm sticks prepared by the same method and evaluated included organoleptic test, homogenity, hardness and melting point. The result showed that difference in melting point and hardness, but all formula meet the requirment of physical preparation balm stick. Formula with VCO and Adeps lanae shows higest melting point and hardness. Statistical result of Kruskal Wallis shows sig <0,05 which means that there were difference of each formula. It could be concluded that VCO with Adeps lanae in combination Carnauba wax and Cera alba g a ve a high melting poin , hardenss and yield value.